Recent development of hybrid organic‐silica monolithic columns in CEC and capillary LC. Issue 1 (6th November 2014) - Ou, Junjie; Liu, Zhongshan; Wang, Hongwei; Lin, Hui; Dong, Jing; Zou, Hanfa; El Rassi, Ziad
<x xml:space="preserve">Abstract</x> As an attractive alternative to organic and silica monoliths, hybrid organic–inorganic monolith somewhat combines the advantages of them, such as high surface area, excellent mechanical strength, and thermal stability. We have reviewed the preparation and application of hybrid monoliths in 2011 and 2013. The preparation approaches have been mainly summarized into three categories: (1) common sol–gel process using trialkoxysilanes and tetraalkoxysilanes as precursors; (2) "one‐pot" process of alkoxysilanes and organic monomers simultaneously via sol–gel chemistry and free radical polymerization; and (3) other polymerization of silane‐containing monomers. Herein, we would focus on the recent progress and development of preparation approaches, mainly covering the literatures since July of 2012. First, the direct synthesis approach of hybrid monoliths via sol–gel chemistry and following postmodification was an important route to fabricate various monolithic stationary phases, particularly, to modify the hybrid monoliths containing amino, epoxy, vinyl, and other groups. Second, "one‐pot" process, as a novel preparation approach of hybrid monoliths, was further developed in the past 2 years, in which various organic functional monomers, not only water‐soluble monomers, but also hydrophobic monomers could be added in the preparation system. Other polymerization techniques in the preparation of organic monolithic materials, particularly, free radical polymerization and ring‐opening polymerization, were successfully transferred to fabricate the hybrid monoliths by using silane‐containing monomers including POSS monomers or other self‐synthesized monomers.